Should the Nordic Countries Join A European Monetary Union? An Empirical Analysis. - U. Michael Bergman; Michael M. Hutchison; Yin-Wong Cheung (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
This paper examines the implications for the Nordic Countries (Denmark, Finland, Norway and Sweden) of participating in the finan stage of the European Monetary Union. Economic linkages with Germany are estimated using a time series approach under both the Bretton Woods and the post-Bretton Woods exchange rate regimes. Output responses of the Nordic countries to permanent and transitory disturbances are estimated and compared with two small core members, Belgium and the Netherlands. We find that the long-standing EU members (Belgium, Denmark and the Netherlands) are closely integrated with Germany in that German shocks have a direct and large impact on their output developments. These linkages appear much weaker for Finland, Norway and Sweden. Common European disturbances also do not distinguish the Nordic countries from the non-Nordic countries.
Keywords: 330